Targeting the Regulatory Subunit R2Alpha of Protein Kinase A in Human Glioblastoma through shRNA-Expressing Lentiviral Vectors - Maira Zorzan; Claudia Del Vecchio; Stefania Vogiatzis; Elisa Saccon; Cristina Parolin; Giorgio Palù; Arianna Calistri; Carla Mucignat-Caretta (Viruses, 2021)
Glioblastoma is the most malignant and most common form of brain tumor, still today associated with a poor 14-months median survival from diagnosis. Protein kinase A, particularly its regulatory subunit R2Alpha, presents a typical intracellular distribution in glioblastoma cells compared to the healthy brain parenchyma and this peculiarity might be exploited in a therapeutic setting. In the present study, a third-generation lentiviral system for delivery of shRNA targeting the regulatory subunit R2Alpha of protein kinase A was developed. Generated lentiviral vectors are able to induce an efficient and stable downregulation of R2Alpha in different cellular models, including non-stem and stem-like glioblastoma cells. In addition, our data suggest a potential correlation between silencing of the regulatory subunit of protein kinase A and reduced viability of tumor cells, apparently due to a reduction in replication rate. Thus, our findings support the role of protein kinase A as a promising target for novel anti-glioma therapies.